2019
DOI: 10.1016/j.ijnss.2019.06.007
|View full text |Cite
|
Sign up to set email alerts
|

A review and comparison of common maternal positions during the second-stage of labor

Abstract: The second-stage of labor is the most stressful part of childbirth process and the proper maternal position during this period is paramount for women's safe vaginal birth. Midwives play a pivotal role in managing maternal positions during the second-stage of labor. However, there is limited evidence to support an ideal maternal position during the second-stage of labor. Further, the difference between different maternal positions might not be apparent. This paper aims to review and compare the benefits and ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
1
30

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(100 citation statements)
references
References 67 publications
2
67
1
30
Order By: Relevance
“…Pelvic mobility is one of the labor factors and permits safe childbirth: the contracted pelvis leads to obstructed labor and operative deliveries [2][3][4][5][6]9,10]. The freedom to move, the standing positions throughout labor, and giving birth in non-recumbent situations allow women to have better comfort during labor and labor to proceed physiologically [9,10]. Studies demonstrated the pelvic space diameters adaptation to patients' postures [2][3][4][5][6].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Pelvic mobility is one of the labor factors and permits safe childbirth: the contracted pelvis leads to obstructed labor and operative deliveries [2][3][4][5][6]9,10]. The freedom to move, the standing positions throughout labor, and giving birth in non-recumbent situations allow women to have better comfort during labor and labor to proceed physiologically [9,10]. Studies demonstrated the pelvic space diameters adaptation to patients' postures [2][3][4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with their statement, our study shows that all the posterior pelvic diameters increase in the "hands-and-knees" position. Hemmerich and colleagues' simulating study had considered a woman's loading conditions on feet squat position without hands support, which is an unusual position for parturients to maintain for a long time [10]. They have emphasized the importance of the squat position on the feet to investigate pelvic biomechanics during the second stage of labor to prevent childbirth complications, such as obstructed labor [5].…”
Section: External Pelvicmentioning
confidence: 99%
See 2 more Smart Citations
“…The women need to have different positions during labour, and delivery like sitting, squatting, walking, standing, and lying down of reducing the labour duration; this also relieves discomfort because of reducing the need for painkillers and operative procedures to aid childbirth. Especially if seen from the angle of gravity it assists in the descent of the baby mainly when the mother assumes upright positions for childbirth (33).…”
Section: Theoretical Frameworkmentioning
confidence: 99%